2001
DOI: 10.4102/curationis.v24i2.835
|View full text |Cite
|
Sign up to set email alerts
|

System requirements for a computerised patient record information system at a busy primary health care clinic

Abstract: A prototyping approach was used to determine the essential system requirements of a computerised patient record information system for a typical township primary health care clinic. A pilot clinic was identified and the existing manual system and business processes in this clinic was studied intensively before the first prototype was implemented. Interviews with users, incidental observations and analysis of actual data entered were used as primary techniques to refine the prototype system iteratively until a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
2
Order By: Relevance
“…Also in the present study, the number of portable computers and the network lines’ speed are semi-desirable to run a NCIS, which is consistent with the result of a Montini (2013) study, reporting lack of portable computers, poor wireless communication and the network lines’ speed in a feasibility study of the backup system of a clinical decision in treating tobacco consumption in a dental clinic ( 29 ). But it is not consistent with the results of other studies that reported; the number of portable computers and the network lines’ speed are adequate ( 17 , 23 , 26 , 30 , 31 ). Given that the study findings show that by using information systems, planning and documentation are enhanced due to the communication and integration with other information systems therefore rapid access to a patient information, documentations are comprehensively presented.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Also in the present study, the number of portable computers and the network lines’ speed are semi-desirable to run a NCIS, which is consistent with the result of a Montini (2013) study, reporting lack of portable computers, poor wireless communication and the network lines’ speed in a feasibility study of the backup system of a clinical decision in treating tobacco consumption in a dental clinic ( 29 ). But it is not consistent with the results of other studies that reported; the number of portable computers and the network lines’ speed are adequate ( 17 , 23 , 26 , 30 , 31 ). Given that the study findings show that by using information systems, planning and documentation are enhanced due to the communication and integration with other information systems therefore rapid access to a patient information, documentations are comprehensively presented.…”
Section: Discussioncontrasting
confidence: 93%
“…In the study of Ozkan (2006) there was no terminal to search web external resources such as PubMed and off-line inquiry software, for users’ support ( 27 ). Blignaut et al (2001) also showed that there was no off-line search facility in the database ( 31 ). In a study that was conducted to evaluate an electronic system to predicate clinical care, while access to computers and technology was provided, new technology tools have not been predicted ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not consistent with the results of some studies that have reported that at the time of information system application, nurses were familiar with computer, felt good when using its tools and easily recovered their data [23,24,42,43]. Blignaut et al (2001) stated that a workshop-like consulting environment helped nurses improve their confidence and familiarity with system before launching a new system [25]. The study of Bond (2007) and Just (2008), conducted in Thailand, reported that nurses familiar with computer skills search their needed information easily and apply them when providing care [22,44].…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, the study of Imani et al (2015) reported that most problems that nurses are faced with happen when working with medical information computer programs due to lack of familiarity with computer science and the lack of adequate training [41]. However, it is not consistent with the results of some studies that have reported that at the time of information system application, nurses were familiar with computer, felt good when using its tools and easily recovered their data [23,24,42,43]. Blignaut et al (2001) stated that a workshop-like consulting environment helped nurses improve their confidence and familiarity with system before launching a new system [25].…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies can be classified as studies with positive attitudes and views and studies with negative attitudes and views [4][5][6][7][8]. These attitudes and views were shown to be affected by several common expectations, such as the ease of use, availability of useful extra features, costs, need for training, and confidentiality and security concerns [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%